Numerical study of tornado-borne debris on a low-rise building through large eddy simulation - Liu, Zhenqing; Cao, Yiwen; Cao, Jinxin; Wang, Yize; Cao, Shuyang (Journal of fluids and structures, 2021)
Tornado-borne debris is considered as a major source of damage. However, effects of tornado-borne debris on buildings have been seldom investigated. This study performed large eddy simulation to reproduce a tornado and examined the characteristics of incident debris on building surfaces, considering two factors: debris diameter (d=2, 5, and 10 cm), and distance between tornado center and building (r). The debris was assumed to be wooden. It has been found that the probability of the debris hitting the building is the highest when d=5 cm, and the debris mainly hit the windward surface and the far-tornado lee-side wall of the building. The downward flying debris is the reason of relatively high intensities of the debris hitting the building roof when r=0. The highest speed of the debris hitting the building occurs when the building is mounted at the core boundary of the tornado, reaching 126 m/s. In addition, interaction between the tornado and building disturbs and accelerates the flying debris. The windward wall of the building experiences the strongest debris hit, with the maximum hitting speed of 102 m/s, 126 m/s, and 188 m/s, when the debris diameter is 2, 5, and 10 cm, respectively. The most dangerous region is identified as the near-core part of windward building surface. •Debris was directly modeled with consideration of turbulence effects in tornado.•Most destructive region in tornado due to debris was identified.•Most dangerous part of the building subject to tornado-induced debris is identified.•PDF of velocities in debris hitting building were examined.